Eros and Thanatos: A Study of Selected English verse - Muhamad, Ranji︎ Shorsh Rauf; Saeed, Ismael Muhamad Fahmi (Sulaimani Journal for Humanities, 2019)
This paper is an extract from a PhD dissertation which is entitled “Eros and Thanatos: A Study in Pelected Poems of Sylvia Plath and Anne Sexton”. Human life is affected by various forces, among which are the instinctual drives, Eros and Thanatos, which are introduced by Sigmund Freud. The two drives are in a constant struggle throughout the life of an individual. This study aims to investigate the effects of the two drives in some English verse. This thesis focuses on the Aristotelian method of persuasion; Pathos, ethos and logos and sheds light on some poems of Sylvia Plath and Anne Sexton which they used these methods to persuade the reader. The death in English poetry has its own significance in this study. Some of English poems which concerns about death are illustrated.
Keywords: Eros; Thanatos; Ethnicity; Ethos; Pathos; Logos